Caracterização e frutificação de um acesso apirênico de pitangueira - Pirola, Kelli (2017)
The native fruit trees have gained attention by producers and consumers, already that it is consider as functional food. In the case of Surinan Cherry tree, it is one of native fruit trees with commercial cultive, it being currently exploited by the juice and cosmetics industry. For the industry, in general, it is important that the Surinan Cherry fruit to present the maximum pulp content. However, the fruits of this specie do not have this characteristic, because they generally produce large seeds comparatively to the fruit size. Nevertheless, there is a genotype that produces fruit withou seed from UTFPR - Câmpus Dois Vizinhos, Paraná State, Brazil, what to change the market, and itcan attracted more fruit growers interested its cultive. But, the causes of this characteristic have to be elucidated for in the future for it be posible have in the market genotypes producing fruit quality superior and without seed. The aim of this work was to elucidate the causes of fruit without seed in the Surinan Cherry (Eugenia uniflora L) and its fruit quality was comparated with of the other Surinan Cherry trees. The works were carried out at the Microscopy and Plant Physiology Laboratories and at the native fruit collection area from UTFPR - Câmpus Dois Vizinhos - Paraná State, Brazil. In addition, to have works at Aula Dei Experimental Station (Zaragoza, Spain). Genotypes of Surinan cherry (Eugeia uniflora L.), which produce fruits with and without seeds (pirenics and apirenic, respectively) it was studied. Experiments were carried out involving floral and reproductive biology of Surinan cherry tree; it was realized histological sections for description of embryogenesis and ontogenesis; levels of ploidy and evaluation of the fruit quality. It can to be observed that the apirenic genotype in many characteristics was not different to pirenic genotype. It was verified that the pirenic genotype presented a longer period of flowering and fruiting and, presented a higher number of pollen by flower compared to apirenic genotype. The apirenic genotype can to serve as a basis for crosses directed in the fruit breeding of Surinan cherry, to try obtaining new hybrids, with this characteristic, already that, this fruit present quality to in nature or industry market.